EVALUATION OF ADR – A PROSPECTIVE ANALYSIS IN A TERTIARY CARE TEACHING HOSPITAL - K.KRANTHI; R.JAMUNA RANI; V.SATHYANARAYANAN (International Journal of Pharma and Bio Sciences, 2016)
Adverse drug reactions are due to hazards of drug therapy and can occur with any class of drugs. The goal of this study was to evaluate and analyze Adverse Drug Reactions in inpatients of a tertiary care hospital (SRM MCH & RC) at Kattankulathur. A prospective analysis and spontaneous reporting study was done from January 2014 to September 2014 – a period of nine months. A total number of 73 ADRs were reported during this nine months period of which 26 were males and 47 were females showing female preponderance. The highest number is from General Medicine followed by General Surgical department. Since allergic reactions most commonly occur in the skin, it is the most commonly affected organ system (52.05%) followed by gastro intestinal system (6.8 %). The most common drugs causing ADRs were antibiotics (49.3 %) of which type B reactions were more common than type A. Most of the reactions were mild (71.6%). Causality assessment was done which showed that 72.6% of the reactions were probable, possible (21.9%), certain (5.47%) and no reactions were unlikely. The study concluded that Adverse Drug Reactions are common and some of them resulted in increased expenditure due to interventions and increased length of hospital stay. Rational and judicious use of drugs is a critical step in preventing ADR as a part of patient management.